2002
DOI: 10.1046/j.1523-1747.2002.01758.x
|View full text |Cite
|
Sign up to set email alerts
|

Positive Atopy Patch Test Reaction to Malassezia furfur in Atopic Dermatitis Correlates with a T Helper 2-like Peripheral Blood Mononuclear Cells Response

Abstract: The yeast Malassezia furfur belongs to the normal cutaneous flora, but is also a triggering allergen that can contribute to atopic dermatitis. To illuminate the effect of circulating allergen-specific T cells in atopic dermatitis, the peripheral mononuclear cell response was correlated with the in vivo skin prick test and atopy patch test reactivity to M. furfur. None of 16 healthy controls showed any positive in vivo reaction. The 40 atopic dermatitis patients, of whom 18 had serum IgE reactivity to M. furfur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 38 publications
1
43
0
Order By: Relevance
“…However, in that study the possible association with allergen-specific IgE was not considered. Later we showed a significantly higher M. sympodialis -specific proliferation and a Th2-like cytokine response in PBMC from ATP-positive versus APT-negative patients (with both patient groups having elevated levels of allergen-specific IgE) [26]. Moreover, in a study to explore the relevance of an in vivo topical challenge method for house dust mite hypersensitivity, Shah et al [27] found that the same 30% of adult IgE+ AE patients that revealed eczema upon in vivochallenge also responded with significantly higher PBMC proliferation upon in vitro allergen challenge.…”
Section: Discussionmentioning
confidence: 99%
“…However, in that study the possible association with allergen-specific IgE was not considered. Later we showed a significantly higher M. sympodialis -specific proliferation and a Th2-like cytokine response in PBMC from ATP-positive versus APT-negative patients (with both patient groups having elevated levels of allergen-specific IgE) [26]. Moreover, in a study to explore the relevance of an in vivo topical challenge method for house dust mite hypersensitivity, Shah et al [27] found that the same 30% of adult IgE+ AE patients that revealed eczema upon in vivochallenge also responded with significantly higher PBMC proliferation upon in vitro allergen challenge.…”
Section: Discussionmentioning
confidence: 99%
“…That finding strongly supports that the T-cell response is another crucial factor for allergen-specific eczema reactions in AE in addition to antigen presentation mediated by specific IgE bound to epidermal Langerhans cells [36, 37]. The lack of positive APT reactions to Malassezia in certain AE patients with serum IgE reactivity to Malassezia may rather be explained by low levels of Malassezia -specific Th2-like T cells [8]than by the blocking of IgG4 antibodies.…”
Section: Discussionmentioning
confidence: 53%
“…We have previously shown that positive APT reactions to Malassezia have a stronger correlation to a Th2-like T-cell response than to elevated levels of Malassezia- specific serum IgE [8]. That finding strongly supports that the T-cell response is another crucial factor for allergen-specific eczema reactions in AE in addition to antigen presentation mediated by specific IgE bound to epidermal Langerhans cells [36, 37].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…The concentrations encountered by mast cells in vivo can only be estimated. However, the extract concentrations used in this study concord with amounts used for atopy patch tests (41) and for in vitro activation of human T cells (42,43). Even if the concentration of M. sympodialis that reaches the IgE receptor cross-linked mast cells in the skin along with other allergens is not sufficient to increase mast cell degranulation, it might still result in IL-6 release, thus enabling an increased Th2 differentiation and thereby promoting allergic inflammation.…”
Section: Discussionmentioning
confidence: 82%